Review of robber flies of the genus Stichopogon Loew (Diptera: Asilidae: Stichopogoninae) from Egypt - El-Hassan, Gawhara M.m. Abu; Badrawy, Haitham B.m.; Allah, Sohair M. Gad; Soliman, Ahmed M.; Salama, Mohamed S.; Mohammad, Salwa K. (Zootaxa, 2017)
The Egyptian fauna of the asilid genus Stichopogon Loew is revised. Nine species are recognized including two new records, Stichopogon deserti Theodor, 1980 and S. scaliger Loew, 1847. A key to species, lists of material examined and their distribution are included. The occurrence of S. maroccanus in Egypt is discussed and clarified.